The problem is escalating: Barriers faced by medical students in conducting research; A scoping literature review - L. Winter Mokhwelepa; G. Olivia Sumbane; Shisana Baloyi; Samuel Risenga; Tumisang Malete (PLoS ONE, 2026)
Background Research is a cornerstone of medical education, equipping future healthcare professionals with critical thinking skills and the ability to apply evidence-based practices. Despite its importance, medical students often encounter numerous obstacles that hinder their active participation in research. These challenges not only affect students’ academic growth but also limit the advancement of medical knowledge and innovation within the healthcare system. Aim This study aimed to review, map, and synthesize the barriers that hinder medical students from engaging in research, and to provide insights that can inform educational reforms and policy interventions to strengthen research capacity among medical students. Methods The authors followed the Joanna Briggs Institute (JBI) Scoping review guidelines. The initial search was conducted in January 2025 and concluded in August 2025. A comprehensive literature search was performed across three major electronic databases: PubMed, Web of Science, and Scopus. The following key terms were used: “medical students”, “research barriers”, “research participation”, “challenges”, and “medical education”. Only peer-reviewed studies published in English between 2010 and 2025 that examined barriers faced by medical students in conducting research were included. Studies focusing on non-medical or postgraduate students, non-English articles, editorials, and abstracts without full texts were excluded. Results Fifty-seven studies met the inclusion criteria. The review identified key barriers hindering medical students’ engagement in research, including limited mentorship, heavy academic workload, and insufficient research training. Institutional challenges such as inadequate funding and poorly structured curricula further restricted participation. Conclusion Improving mentorship, research training, and institutional support is crucial to empower medical students and foster greater engagement in research.